STUDI TEKNOLOGI DAN KELAYAKANUSAHA TAPE SINGKONG DI DESA KETANGI KECAMATAN KARANGPLOSO KABUPATEN MALANG - Riyanto Djoko; Fauzia Hulopi; Hariadi Darmawan (Universitas Tribhuwana Tunggadewi, 2016)
Mr. Wandi and Mr. Amari is a fermented cassava businesses in the rural Ketangi, Karangploso subdistrict, Malang regency are currently experiencing difficulties in maintaining and developing a business. This happens because of limited capital and limited marketing reach. Technology production is still modest, less sterile and production equipment are just packed in a plastic bag or use a bowl.Appropriate technology improvement efforts of both businesses fermented cassava in the rural Ketangi be hygienic equipment that can guarantee the sterility of the product, use a wheelbarrow / tricycles can expand the reach of the marketing and use of packaging plastic boxes can improve the quality and value of selling the fermented cassava. Applied technology is a technology that is simple and easy to operate.The application of appropriate technology improvements can increase revenues both businesses fermented cassava approximately 35% to 50%, as well as the pilot for the surrounding community.